Cherry Valley Duck Galectin-2 Plays an Essential Role in Avian Pathogenic Escherichia coli Infection-Induced Innate Immune Response - Li, Tianxu; Weng, Hongyu; Lin, Jing; Zhang, Tingting; Zhang, Huihui; Song, Xingdong; Hou, Xiaolan; Wei, Liangmeng (Frontiers in Veterinary Science, 2020)
Galectins play important roles in the host's innate immunity as pattern recognition receptors. In this study, the coding sequences of galectin-2 were identified from Cherry Valley ducks. Tissue distribution of duck galectin-2 (duGal-2) in healthy ducks and ducks infected with avian pathogenic Escherichia coli (APEC) was studied, respectively. The results showed that duGal-2 expression was higher in the gut, kidney, and liver tissue, and weakly expressed in the lung and brain, in healthy ducks; however, the expression level of duGal-2 was detected as being up-regulated after infection with APEC. In addition, knockdown or overexpression of duGal-2 in DEFs was achieved by small interference RNA (siRNA) transfection and plasmid transduction, respectively. The knockdown of duGal-2 led to a decrease in the expression of some inflammatory cytokines such as IL-1β, IL-6, and IL-8, while the expression levels of anti-inflammatory factor IL-10 were up-regulated. At the same time, the bacterial load of APEC was increased after knockdown of duGal-2 in vitro. However, the opposite results were obtained in the duGal-2 overexpression group. Taken together, duGal-2 plays an important role in the host against APEC infection.